Caves and karst of Ecuador – state-of-the-art and research perspectives. (2nd January 2019) - Constantin, Silviu; Toulkeridis, Theofilos; Moldovan, Oana Teodora; Villacís, Marcos; Addison, Aaron
Abstract: Current knowledge of caves and karst regions of Ecuador is scarce and broadly limited to discrete areas such as that of the Galápagos volcanokarst. In continental Ecuador, carbonate karst mostly outcrops in the Amazonian basin and accounts for 5–10% of the surface of the country. However, owing to the difficulties of access within the Amazonian rainforest, most surface and subterranean karst is yet to be revealed. In this review, we present an updated map of the solutional karst of Ecuador based on the most recent geological surveys and our own research. We describe the principal karst regions of Ecuador from the Amazonian basin (Napo and Santiago) as well as the Galápagos pseudokarst. We show that Ecuador karst research may be of considerable importance for both basic and applied research owing to its geographical position and intrinsic vulnerabilities. We discuss the main challenges of karst-related research in Ecuador, such as paleoclimatic studies, subterranean biodiversity, and archeology. We discuss the main vulnerabilities and hazards related to karst uses in Ecuador, considering the paramount importance of tourism for the country.